2021
DOI: 10.1016/j.paid.2021.110913
|View full text |Cite
|
Sign up to set email alerts
|

Big Five traits, approach-avoidance motivation, concerns and adherence with COVID-19 prevention guidelines during the peak of pandemic in Croatia

Abstract: Without the vaccine, the only way to prevent the spread of coronavirus is following Covid-19 preventive guidelines such as keeping social distance, wearing masks and gloves, reducing mobility, etc. Success depends on how many individuals strictly follow the suggestions from epidemiologists. In this study, we examined who and why is adhering to the guidelines. A community sample of 500 participants fulfilled a short Big Five Inventory (BFI), Questionnaire of Approach and Avoidance Motivation (QAAM), and two sca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 37 publications
5
34
1
Order By: Relevance
“…However, agreeableness and openness were associated with adherence. This is largely in line with previous findings, although associations with conscientiousness and neuroticism have sometimes also been reported (AL-Omiri et al, 2021;Aschwanden et al, 2021;Blagov, 2021;Brouard et al, 2020;Clark et al, 2020;Imhoff & Lamberty, 2020;Krupić et al, 2021;Wright et al, 2021;Zajenkowski et al, 2020). We showed that agreeableness and openness were still associated with adherence when controlling for acceptance.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, agreeableness and openness were associated with adherence. This is largely in line with previous findings, although associations with conscientiousness and neuroticism have sometimes also been reported (AL-Omiri et al, 2021;Aschwanden et al, 2021;Blagov, 2021;Brouard et al, 2020;Clark et al, 2020;Imhoff & Lamberty, 2020;Krupić et al, 2021;Wright et al, 2021;Zajenkowski et al, 2020). We showed that agreeableness and openness were still associated with adherence when controlling for acceptance.…”
Section: Discussionsupporting
confidence: 93%
“…Among these are the Big 5, a basic model of personality traits (e.g., Costa & McCrae, 1992). Previous studies suggest weak positive associations with compliance to the preventive measures for agreeableness, openness, conscientiousness and neuroticism, and a negative association for extraversion, but results were not always consistent (AL-Omiri et al, 2021;Aschwanden et al, 2021;Brouard et al, 2020;Clark et al, 2020;Imhoff & Lamberty, 2020;Krupić et al, 2021;Wright et al, 2021;Zajenkowski et al, 2020). Beside these direct effects, various indirect effects are conceivable, such as a positive association between neuroticism and fear of getting infected with SARS-CoV-2 , or between conspiracy beliefs and low agreeableness and high openness to experience and neuroticism (e.g., Bruder et al, 2013;Goreis & Voracek, 2019;Swami et al, 2010Swami et al, , 2013, although the exact relationship between the Big 5 variables and conspiracy beliefs has remained controversial (Bowes et al, 2021).…”
Section: Classical Personality-related Variables: Big 5 Locus Of Control Optimism-pessimismmentioning
confidence: 96%
See 1 more Smart Citation
“…Given the undeniable importance of adhering to the preventive measures for the prevention of SARS-CoV-2 spread, researchers have begun to study psychological variables that may explain individual differences in response to the preventive measures. It has for example been shown that high levels of fear of getting infected with SARS-CoV-2 (e.g., Carlucci et al, 2020;Jiwani et al, 2021;Kachanoff et al, 2021;Plohl & Musil, 2021;Reinders Folmer et al, 2020;Rothgerber et al, 2020;Vally, 2020), or the Big 5 personality traits agreeableness, openness, and conscientiousness (e.g., Brouard et al, 2020;Krupić et al, 2021;Wright et al, 2021) are associated with higher adherence to the COVID-19 preventive measures. The opposite is true for high levels of impulsiveness, mistrust in science or the government, or political conservatism (e.g., Plohl & Musil, 2021;Reinders Folmer et al, 2020;Rothgerber et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Self-management is an indispensable criterion for the successful completion of such tasks and is attributed to individuals with a high degree of conscientiousness (Lamond, 2000). Concerning the compliance with pandemic restrictions, conscientious people are expected to have fewer problems with restrictions due to the pronounced conformity to rules and their sense of responsibility (Krupić et al, 2021). Also, conscientiousness helps to withstand the negative psychological influence of the COVID-19 pandemic (Zhang et al, 2021).…”
Section: The Influence Of the Big Five Of Personality During The Covid 19 Pandemicmentioning
confidence: 99%